Persepsi Pelajar Terhadap Perkhidmatan Bimbingan dan Kaunseling - Azhari, Abd. Rahman (1998)
This study is intended to explain the perceptions of secondary school students as regards to the counselling and guidance service provided in schools, particularly their function, capabilities and effectiveness. Apart from that, the study is also intended to determine the difference, if any, in perception between the urban and rural students and between the male and female students, towards the counselling and guidance services. The sampling for this study consisted of 368 Form Five students from six secondary grade A school in the Kota Setar District, Kedah Darul Aman. A questionnaire was used to gather the necessary data. To elicit the necessary response, a set of questionnaire consisting of Likert style 4-scale items was distributed. All the data gathered was analyzed using descriptive statistics and T-test. The findings indicated that the perception of the respondents towards the counselling and guidance service was positive. The comfort and physical facilities in the counselling rooms, the personality of the school counsellors, his capabilities in solving students’ problems, guidance in upgrading academic performances, and entry into institutions of higher learning, career guidance, and confidence of students towards the counselling and guidance. The results of this study also showed that there were no significant difference in perception between male and female students, but a significant difference in perception was noted between the urban and rural students towards the counselling and guidance services. Based on the findings, it is suggested that the counselling and guidance services be retained and further improved. The services provided in urban school should be improved to meet the same standard as the rural schools. Aspects that should be given particular attention are the comfort and physical facilities of the counselling rooms, guidance in raising academic performances, and entrance into institutions of higher learning.